Medical Education and Safety as Co-priorities in the Coronavirus Disease 2019 (COVID-19) Era: We Can Do Both. Issue 4 (October 2020) - Baecher-Lind, Laura; Fleming, Angela C.; Bhargava, Rashmi; Cox, Susan M.; Everett, Elise N.; Graziano, Scott C.; Katz, Nadine T.; Sims, Shireen Madani; Morgan, Helen K.; Morosky, Christopher M.; Sonn, Tammy S.; Sutton, Jill M.; et al.
Abstract : As hospitals and medical schools confronted coronavirus disease 2019 (COVID-19), medical students were essentially restricted from all clinical work in an effort to prioritize their safety and the safety of others. One downstream effect of this decision was that students were designated as nonessential, in contrast to other members of health care teams. As we acclimate to our new clinical environment and medical students return to the frontlines of health care, we advocate for medical students to be reconsidered as physicians-in-training who bring valuable skills to patient care and to maintain their status as valued team members despite surges in COVID-19 or future pandemics. In addition to the contributions students provide to medical teams, they also serve to benefit from the formative experiences of caring for patients during a pandemic rather than being relegated to the sidelines. In this commentary, we discuss factors that led to students' being excluded from this pandemic despite being required at the bedside during prior U.S. public health crises this past century, and we review educational principles that support maintaining students in clinical environments during this and future pandemics. Abstract : Clinical medical student education must remain a priority as health care organizations adjust to a new clinical environment during the coronavirus disease 2019 (COVID-19) pandemic.